Prominent genetic structure across native and introduced ranges of Pluchea indica, a mangrove associate, as revealed by microsatellite markers. (25th May 2020) - Lin, Yuting; Banerjee, Achyut Kumar; Wu, Haidan; Tan, Fengxiao; Feng, Hui; Tan, Guangwen; Guo, Wuxia; Huang, Yelin
Abstract: Aims: Pluchea indica is a mangrove-associate species, known for its medicinal properties in its native range and being invasive in part of its introduced range. This study aimed to assess geographic distribution of genetic variation of this species across its distribution range, identify the factors influencing its genetic structure and use this information to suggest conservation and management strategies in its native and introduced ranges, respectively. Methods: We assessed the genetic diversity and population structure of 348 individuals from 31 populations across its native (Asia) and introduced (USA) ranges for 15 nuclear microsatellite loci. The spatial pattern of genetic variation was investigated at both large and regional spatial scales with the hypothesis that geographic distance and natural geographic barriers would influence the population structure with varying levels of differentiation across spatial scales. Important Findings: We found relatively high genetic diversity at the population level and pronounced genetic differentiation in P. indica, as compared with the genetic diversity parameters of mangroves and mangrove associates in this region. Most of the populations showed heterozygote deficiency, primarily due to inbreeding and impediment of gene flow. Analysis of population structures at large spatial scale revealed the presence of two major clusters across the species' natural range separating populations in China from those in Indonesia, Malaysia, Singapore, Thailand, Cambodia and Philippines, and that the USA population might have been introduced from the population cluster in China. Genetic differentiation between populations was also observed at the regional scale. A large number of populations showed evidence of genetic bottleneck, thereby emphasizing the risk of local extinction. Based on these findings, our study recommends in situ conservation strategies, such as to prioritize populations for conservation actions and to maintain genetic diversity.